One-year cognitive follow-up in patients hospitalized for COVID-19 in a cohort from Mexico - Rodríguez-Agudelo Yaneth; Paz-Rodríguez Francisco; Chávez-Oliveros Mireya; Lozano-Tovar Susana; Rodríguez-Rodríguez Mónica; Soto-Moreno Francisco-Javier; García-Santos Anwar; López-González Diana; González-Navarro Mauricio; Fuentes-Dominguez Mauro Fernando; Carrillo-Mezo Roger; Marrufo-Meléndez Oscar; et al. (Brain Disorders)
Cognitive symptoms have been identified as a prevalent sequela of Covid-19 disease, that it they persist beyond the acute phase of infection. This situation has consequences for the general and emotional functionality of patients. The aim of this work was to explore the prevalence of both global and specific impairments in various cognitive domains in a group of SARS-CoV-2 infection survivors with subjective memory-related complaints from the COVID-19 clinic of the National Institute of Respiratory Diseases. Study subjects underwent a neuropsychological assessment three months after hospital discharge (first assessment T1) and again twelve months later (second assessment T2). The results show that although in the second assessment there was a significant improvement (p < 0.05) in several domains: attention, gnosias, visual memory and language, however, we noted a high persistence of impairments in executive functions (20.8 % at T2). On the other hand, in the analysis of the complete assessment we observed deficits in at least three tests, 73.7 % at T1 and 60.4 % at T2. While in memory and semantic and phonological verbal fluency tasks, we observed improvement without being statistically significant. Our results show that although symptoms such as depression and anxiety decreased significantly, cognitive impairment may still be observed after one year, so we suggest that those patients with severe COVID-19 should receive cognitive follow-up through periodic cognitive assessments.